GABAA receptor-mediated input change on orexin neurons following sleep deprivation in mice. (22nd January 2015) - Matsuki, T.; Takasu, M.; Hirose, Y.; Murakoshi, N.; Sinton, C.M.; Motoike, T.; Yanagisawa, M.
Highlights: GABAA R α1 expression is increased in orexin neuron following 6-h sleep deprivation. Sleep deprivation enhances the sensitivity of orexin neuron to GABAA R agonist. Inhibitory synapses on orexin neuron are profoundly affected by sleep deprivation. Abstract: Orexins are bioactive peptides, which have been shown to play a pivotal role in vigilance state transitions: the loss of orexin-producing neurons (orexin neurons) leads to narcolepsy with cataplexy in the human. However, the effect of the need for sleep (i.e., sleep pressure) on orexin neurons remains largely unknown. Here, we found that immunostaining intensities of the α1 subunit of the GABAA receptor and neuroligin 2, which is involved in inhibitory synapse specialization, on orexin neurons of mouse brain were significantly increased by 6-h sleep deprivation. In contrast, we noted that immunostaining intensities of the α2, γ2, and β2/3 subunits of the GABAA receptor and Huntingtin-associated protein 1, which is involved in GABAA R trafficking, were not changed by 6-h sleep deprivation. Using a slice patch recording, orexin neurons demonstrated increased sensitivity to a GABAA receptor agonist together with synaptic plasticity changes after sleep deprivation when compared with an ad lib sleep condition. In summary, the GABAergic input property of orexin neurons responds rapidly to sleep deprivation. This molecular response of orexin neurons may thus play a role in the changes that accompany the need for sleep following prolonged wakefulness, in particular the decreased probability of a transition to wakefulness once recovery sleep has begun.